Assessment and Evaluation of Canva-Based Comic Strip Media with KEMP Instructional on Sound Material - Risa Faurenza; Rian Vebrianto; Herlinda; Adisti (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Teachers need to make more use of learning media by exploring the important role of media in promoting and limiting information in the educational environment. This study aimed to create Canva-based comic strip media with Kemp's instruction on sound material. Research and development (R&D) is the research methodology used in this study. The research subjects were 15 teachers and 30 students. The data collection method used Google Forms and direct meetings with the respondents involved. The instrument used was a questionnaire. The findings of media evaluation and analysis were analyzed descriptively using SPSS. The results showed expert validation or certified teachers of 4.54, teacher practicality of 4.8, and students of 4.57. The results showed that the learning media was reliable, effective, and efficient in teaching and learning. The research concludes that Canva-based e-comic media with Kemp Instruction on sound material is effective and efficient when teaching, especially on special sound material. This research implies that using visual media can become more important and impact curriculum development by considering the integration of Canva-based comic strip media in teaching sound material.